Encyclopedia of Adolescence 2016
DOI: 10.1007/978-3-319-32132-5_211-2
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and Reactive Aggression

Abstract: Although some question the utility of distinguishing between proactive and reactive aggression, these subtypes represent distinct functions of aggression that differentially relate to a host of child and adolescent outcomes. This essay reviews the research relating to these different functions of aggression and their associated outcomes. These functions and outcomes are important to distinguish for many reasons, not the least of which is to help develop targeted prevention and intervention strategies for adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…The assessment of stressful life events might extend beyond inquiring about experienced stressful life events, as the current results suggest that stressful life events that were witnessed also have an effect on outcomes. The positive association between experienced stressful life events and reactive aggression suggests that clinic work with those exposed to higher levels of experienced stressful life events might include monitoring strategies and cognitive behavioral techniques (Fite et al, 2016). If witnessing sexual victimization and other interpersonal forms of trauma indeed increase the risk of proactive and reactive aggression, as the current results might indicate, clinical interventions might aim to improve perception and interpretation of social information, lower sensitization to threats, and provide skills training centered on generating alternative methods of obtaining goals, which have been indicated in the treatment of proactive and reactive aggression (Fite et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of stressful life events might extend beyond inquiring about experienced stressful life events, as the current results suggest that stressful life events that were witnessed also have an effect on outcomes. The positive association between experienced stressful life events and reactive aggression suggests that clinic work with those exposed to higher levels of experienced stressful life events might include monitoring strategies and cognitive behavioral techniques (Fite et al, 2016). If witnessing sexual victimization and other interpersonal forms of trauma indeed increase the risk of proactive and reactive aggression, as the current results might indicate, clinical interventions might aim to improve perception and interpretation of social information, lower sensitization to threats, and provide skills training centered on generating alternative methods of obtaining goals, which have been indicated in the treatment of proactive and reactive aggression (Fite et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The existing evidence base suggests that stressful life events predict concurrent and subsequent levels of aggression (Owen et al, 2004). However, aggression is a complex and multifaceted construct, with research consistently providing support for the distinction between proactive and reactive aggression (Fite et al, 2016). Rooted in social learning theory, proactive aggression is a goal oriented and premediated form of aggression that is modeled and governed by reinforcement contingencies (Fite et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proactive aggression is positively associated with callous-unemotional traits (i.e., a lack of guilt and remorse; Barry et al 2007;Fite et al 2009Fite et al , 2010 and unrelated to emotional arousal (Hubbard et al 2004(Hubbard et al , 2010. It appears that proactive aggression does not elicit the same negative emotions that produces anxiety (Fite et al 2010(Fite et al , 2012Raine et al 2006;Vitaro and Brendgen 2011) and ultimately results in sleep difficulties that reactive aggression elicits.…”
Section: Discussionmentioning
confidence: 90%
“…Supporting this notion, Waschbusch and Willoughby (1998) found that reactive, not proactive, aggression was associated with classroom rule violations. Further, proactive aggression has been more strongly linked to antisocial outcomes than reactive aggression (Fite et al, 2016; Vitaro & Brendgen, 2012). However, more research in this area is needed before conclusions regarding associations can be drawn.…”
Section: Proactive and Reactive Aggression And Disciplinary Actionsmentioning
confidence: 99%